Drilling Down in Norm Diffusion: Norm Domestication, "Glocal" Power, and Community-Based Organizations in Global Health. Issue 3 (22nd September 2021) - Restoy, Enrique; Elbe, Stefan
ABSTRACT: Norm diffusion scholarship analyzes how states come to agree and adopt new international norms. Yet, formal adoption of a new norm does not in itself guarantee that a government will also implement it domestically, and very little international relations scholarship drills down deep enough to examine whether and how new international norms are subsequently integrated, incorporated, and translated at sub-state level. This article initiates a research agenda on norm "domestication" through the first in-depth study of how international norms in the field of global health are locally incorporated by community-based organizations (CBOs). Drawing upon multi-sited international fieldwork in Uganda, Ukraine, and El Salvador, the paper uncovers three norm domestication strategies used by CBOs of people affected by HIV/AIDS: harnessing political divisions within national governments, circumventing government policy with international help, and mounting legal challenges to government policy. The article argues that these CBO strategies represent "glocal" forms of power capable of forging local–global connections through combined practices of norm allying, norm implementation, and norm intertwining. These subtler processes of norm domestication, the article concludes, ultimately require a reconceptualization of norm diffusion not just as a transnational phenomenon, but as a "multi-local" process during which norms are concurrently localized across diverse geographic locales.